The limited immunomodulatory effects of escharectomy on the kinetics of endotoxin, cytokines, and adhesion molecules in major burns - Tae-Hyung Han; Soo-Yeon Lee; Jung-Eun Kwon; In-Suk Kwak; Kwang-Min Kim (Mediators of Inflammation)
ESCHARECTOMY has been shown to improve the survival rates and the outcomes in burns. This observational study was conducted to assess the role of escharectomy on the inflammatory mediators in major burns. Seventeen ASA physical status II or status III adult surviving major burn patients were recruited. When the escharectomy was scheduled, a series of blood samples was obtained at −3 and −1 days preoperation, and +1 and +3 postoperation. The changing levels of endotoxin, cytokines, and adhesion molecules were measured with a quantitative sandwich immunoassay. Extensive escharectomy did not appear to have any significant impact on the levels of tumor necrosis factor alpha, interleukin-10, soluble intracellular adhesion molecule-1 and soluble vascular adhesion molecule-1. Meanwhile, endotoxin and E-selectin were significantly decreased after escharectomy. Escharectomy appeared to have a limited immunomodulatory effect on the inflammatory mediators in systemic inflammatory responses induced by major burns. This is probably related to the timing and extent of surgery, and the complex nature of burn-related inflammation.